Socioeconomic benefits of high-speed broadband availability and service adoption: A survey - Wolfgang Briglauer; Jan Krämer; Nicole Palan (EcoAustria - Institute for Economic Research, 2023)
Ubiquitous high-speed fiber-based and mobile broadband availability is a key economic policy goal in the European Union and other developed countries. Policymakers seek to boost economic growth, productivity, and employment, especially in remote areas, through ambitious broadband targets and substantial public funding. This paper reviews the existing (empirical) literature on high-speed broadband internet and its socioeconomic impact on key outcome variables. Our main findings are that (i) the socioeconomic benefits in terms of economic growth, productivity, house prices, and education, as well as economic resilience, are high but are also subject to diminishing returns beyond a certain broadband quality level, (ii) the effects on employment are more ambiguous, (iii) the positive socioeconomic effects take hold only after broadband adoption on the demand side, but not with mere availability on the supply side, and (iv) the effects of broadband differ significantly for urban vs. rural and high-skilled vs. low-skilled workers. Based on these findings, we develop recommendations for a cost-effective and efficient broadband policy and future funding regime.
Keywords: 330; High-speed broadband; broadband availability; broadband adoption; fiber connections; mobile broadband; economic benefits; survey